Revealing the genome of the microsporidian Vairimorpha bombi, a potential driver of bumble bee declines in North America - Webster,VL; Hemmings,S; Pérez,M; Fisher,MC; Brown,MJF; Farrer,RA (G3: Genes, Genomes, Genetics, 2024)
Pollinators are vital for food security and the maintenance of terrestrial ecosystems. Bumblebees are important pollinators across northern temperate, arctic, and alpine ecosystems, yet are in decline across the globe. Vairimorpha bombi is a parasite belonging to the fungal class Microsporidia that has been implicated in rapid declines of bumblebees in North America, where it may be an emerging infectious disease. To investigate the evolutionary basis of pathogenicity of V. bombi, we sequenced and assembled its genome using Oxford Nanopore and Illumina technologies and performed phylogenetic and genomic evolutionary analyses. The genome assembly for V. bombi is 4.73 Mb, from which we predicted 1,870 protein coding genes and 179 tRNA genes. The genome assembly has low repetitive content and low GC content. V. bombi's genome assembly is the smallest of the Vairimorpha and closely related Nosema genera, but larger than those found in the Encephalitozoon and Ordospora sister clades. Orthology and phylogenetic analysis revealed 18 core conserved single-copy microsporidian genes including the Histone acetyltransferase (HAT) GCN5. Surprisingly, V. bombi was unique to the microsporidia in not encoding the 2nd predicted HAT ESA1. The V. bombi genome assembly annotation included 265 unique genes (i.e., not predicted in other microsporidia genome assemblies), 20% of which encode a secretion signal, which is a significant enrichment. Intriguingly, of the 36 microsporidian genomes we analysed, 26 also had a significant enrichment of secreted signals encoded by unique genes, ranging from 6% to 71% of those predicted genes. These results suggest that microsporidia are under selection to generate and purge diverse and unique genes encoding secreted proteins, potentially contributing to or facilitating infection of their diverse hosts. Furthermore, V. bombi has 5/7 conserved Spore Wall Proteins (SWPs) with its closest relative V. ceranae (that primarily infects honeybees), while als